2015
DOI: 10.1016/j.ygyno.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

HER2 over-expressing high grade endometrial cancer expresses high levels of p95HER2 variant

Abstract: Background-Subsets of high grade endometrial cancer (EnCa) over-express HER2 (ERBB2), yet clinical trials have failed to demonstrate any anti-tumor activity utilizing trastuzumab, an approved platform for HER2 positive breast cancer (BrCa). A truncated p95HER2 variant lacking the trastuzumab binding site may confer resistance. The objective of this investigation was to characterize the expression of the p95HER2 truncated variant in EnCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A reclassification of risk based on the molecular features is strongly needed for EC subgroups, such as the high-grade (G3) EEC, that have never been clearly classified according to dualistic model of EC. [31][32][33][34] Over the last 3 years, few groups 11,[35][36][37][38] have investigated the prognostic value of different molecular alterations involved in endometrial carcinogenesis, demonstrating that the genomic features of ECs allow for a more reproducible and accurate risk reclassification, which may help in choosing the most appropriate surgical and adjuvant treatment for women with aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A reclassification of risk based on the molecular features is strongly needed for EC subgroups, such as the high-grade (G3) EEC, that have never been clearly classified according to dualistic model of EC. [31][32][33][34] Over the last 3 years, few groups 11,[35][36][37][38] have investigated the prognostic value of different molecular alterations involved in endometrial carcinogenesis, demonstrating that the genomic features of ECs allow for a more reproducible and accurate risk reclassification, which may help in choosing the most appropriate surgical and adjuvant treatment for women with aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data in patients with HER2 amplified breast cancer revealed that patients with truncated p95HER2 were less responsive to HER2 therapy with trastuzumab [24]. Data recently presented at the Society for Gynecologic Investigation suggested that p95HER2 commonly occurs in patients with uterine serous carcinoma [25]. Other reports have suggested that HER2/neu amplified uterine serous carcinomas have the ability to shed soluble free receptor into the interstitial milieu [26].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the binding of therapeutic antiā€HERā€2 antibodies on HERā€2 ECD neutralizes the biological activity of trastuzumab . Furthermore, amounts of HERā€2 ECD shedding leaves a truncated HERā€2 form (p95) with constitutive kinase activity that can provide ligandā€independent growth and survival signals to the cells . Therefore, serum HERā€2 ECD could be a biomarker that helps to identify the subgroup of poorer outcome among HERā€2 overexpression breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%